Advances in Omic Studies Drive Discoveries in the Biology of Anisakid Nematodes - D’Amelio, Stefano (Genes (Basel), 2020)
Advancements in technologies employed in high-throughput next-generation sequencing (NGS) methods are supporting the spread of studies that, combined with advances in computational biology and bioinformatics, have greatly accelerated discoveries within basic and biomedical research for many parasitic diseases. Here, we review the most updated “omic” studies performed on anisakid nematodes, a family of marine parasites that are causative agents of the fish-borne zoonosis known as anisakiasis or anisakidosis. Few deposited data on Anisakis genomes are so far available, and this still hinders the deep and highly accurate characterization of biological aspects of interest, even as several transcriptomic and proteomic studies are becoming available. These have been aimed at discovering and characterizing molecules specific to peculiar developmental parasitic stages or tissues, as well as transcripts with pathogenic potential as toxins and allergens, with a broad relevance for a better understanding of host–pathogen relationships and for the development of reliable diagnostic tools.